DESAIN DIDAKTIS UNTUK PRAKTIK REFLEKSI GURU MATEMATIKA DALAM KOMUNITAS: Sebuah Studi Didactical Design Research (DDR) dan Didactic Mathematical Knowledge (DMK) - Rudi, Rudi (2021)
ABSTRACT One of the problems in realizing the quality of mathematics learning is the student learning obstacles. In order to overcome students' learning obstacles, it takes the development of teacher professionalism in producing teaching material designs. The practice of teacher reflection in the community is one form of teacher professional development. Didactical Design Research (DDR) is a methodological framework to produce teaching material designs and a framework for implementing reflection practices. Didactic Mathematical Knowledge (DMK) is a theoretical framework for teachers' knowledge that can be used to analyze reflective practice activities. This study attempts to produce a didactic design for the practice of reflection on mathematics teachers in the community using the DDR and DMK framework. The method used in this research was DDR with the technique of collecting data through tests, interviews, observation, documentation, a document study, learning recording, and triangulation. Participants in this study consisted of 178 students and 13 mathematics teachers in Takalar Regency, South Sulawesi Province. The analysis of data used four stages of qualitative data analysis developed by Miles and Huberman. The results of this study were the didactic design formulation of the Pythagorean theorem material obtained through the four stages of DDR, namely preparation of reflective practice, planning design/reflection for action/prospective analysis, implementation of design/reflection in action/metapedadidactic analysis, and reflection and evaluation design/reflection off action/retrospective analysis. Also, this study analyzed the implementation of the reflective practice of mathematics teachers in the community using metadidactic analysis and didactic transposition. Keywords: didactical design research, didactic mathematical knowledge, mathematics teachers' community, reflective practice, didactical transposition. ABSTRAK Salah satu permasalahan dalam mewujudkan pembelajaran matematika berkualitas adalah hambatan belajar siswa. Dalam mengatasi hambatan belajar siswa, dibutuhkan pengembangan profesionalisme guru dalam menghasilkan desain materi ajar. Praktik refleksi guru dalam komunitas merupakan salah satu bentuk pengembangan profesionalisme guru. Didactical Design Research (DDR) merupakan salah satu kerangka metodologi untuk menghasilkan desain materi ajar dan kerangka kerja pelaksanaan praktik refleksi. Didactic Mathematical Knowledge (DMK) merupakan salah satu kerangka teori pengetahuan guru yang bisa digunakan untuk menganalisis kegiatan praktik refleksi. Tujuan penelitian ini adalah menghasilkan desain didaktis untuk praktik refleksi guru matematika dalam komunitas menggunakan kerangka DDR dan DMK. Metode yang digunakan dalam penelitian ini adalah DDR dengan teknik pengumpulan data melalui tes, wawancara, observasi, dokumentasi, studi dokumen, catatan pembelajaran, dan triangulasi. Partisipan dalam penelitian ini terdiri dari 178 orang partisipan siswa dan 13 orang partisipan guru matematika di Kabupaten Takalar. Analisis data penelitian menggunakan empat tahapan analisis data kualitatif yang dikembangkan Miles dan Huberman. Hasil dari penelitian ini adalah rumusan desain didaktis empiris materi teorema Pythagoras yang diperoleh melalui empat tahapan DDR, yaitu persiapan praktik refleksi, perencanaan desain/refleksi untuk Tindakan/analisis prospektif, implementasi desain/refleksi dalam indakan/analisis metapedadidaktik, dan refleksi dan evaluasi desain/refleksi setelah Tindakan/analisis retrospektif. Selain itu, penelitian ini juga menganalisis pelaksanaan praktik refleksi guru matematika dalam komunitas menggunakan analisis metadidaktik dan transposisi didaktik. Kata Kunci: Didactical design research, didactic mathematical knowledge, komunitas guru matematika, praktik refleksi, transposisi didaktis